An analytical study on the inclusion of economics in the curriculum of religious schools (madaris) - Muhammad Atta ul Mustafa; Prof. Dr. Fazal Elahi khan (`, 2025)
The study is an analytical study on the issue of incorporating economics into the curriculum of religious seminaries (madaris diniyah) and the need to do it, the advantages which it may have, and how it can be done practically. In the Muslim world, the religious seminaries existed in Asia, especially South Asia and specialized in classical Islamic sciences including Quran, Hadith, Fiqh and Tafsir. Nevertheless, lack of modern sciences such as economics has led to under-preparedness of the graduates in dealing with the current economic issues and becoming financially independent. The research has highlighted that infusion of the economic aspect especially that of Islamic economics has the capability of enlightening students with the useful knowledge needed in the contemporary society and at the same time remain religious. The Islamic economics, unlike the conventional ones, favors values of justice, equity and non-interest deals. The argument made in the research is that through knowledge in economic fundamentals and Islamic financial system, it would be possible to use students to undermine poverty, foster enterprise, and ensure good ethics in business. Comparison of Islamic and modern economics, principles of Quranic and Hadith-based economy and the applications of Islamic tools of finance like zakat, mudarabah, and takaful are also included in the study. It also points out the successful examples of other countries such as Malaysia and Turkey to make the religious schools teach subjects that are modern. Besides, the areas of career opportunities of the seminary graduates are investigated, such as Islamic banking, policy research, and ethical consultancy. These include resistance of tradition, shortage of trained teachers, and the desire of modern educational aids. The conclusion of the study is that introduction of economics in madaris will not only improve the practical skills of students and financial literacy but will also be beneficial in increasing the wellbeing of the whole society and economic growth. The strategy promotes the balanced model of education which harmonizes the religious values and the contemporary economic knowledge. Keywords: Religious Seminaries, Islamic Economics, Curriculum Reform, Financial Self-Reliance, Islamic Banking